The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1016/j.celrep.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Interneurons Differentially Shape Frequency Tuning following Adaptation

Abstract: Neuronal stimulus selectivity is shaped by feedforward and recurrent excitatory-inhibitory interactions. In the auditory cortex (AC), parvalbumin- (PVs) and somatostatin-positive (SOMs) inhibitory interneurons differentially modulate frequency-dependent responses of excitatory neurons. Responsiveness of neurons in AC to sounds is furthermore dependent on stimulus history. We found that inhibitory effects of SOMs and PVs diverged as a function of adaptation to temporal repetition of tones. Prior to adaptation, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 35 publications
11
93
0
Order By: Relevance
“…On the other hand, it cannot be ruled out that after spending longer periods in the absence of SSTi, changes in the locomotor, emotional or pain sensitivity parameters would take place. As mentioned before, SSTi are regulators of adaptive properties (Natan et al., ) and their loss for longer periods, although speculative, could result in escalating behavioural changes over time.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, it cannot be ruled out that after spending longer periods in the absence of SSTi, changes in the locomotor, emotional or pain sensitivity parameters would take place. As mentioned before, SSTi are regulators of adaptive properties (Natan et al., ) and their loss for longer periods, although speculative, could result in escalating behavioural changes over time.…”
Section: Discussionmentioning
confidence: 95%
“…*p < .05, **p < .01. [Colour figure can be viewed at wileyonlinelibrary.com] of adaptive properties (Natan et al, 2017) and their loss for longer periods, although speculative, could result in escalating behavioural changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…Linear fits across frequencies. Linear fits were calculated using linear regression (fitlm.m; MATLAB) over 50 data points, one for each of the 50 frequencies tested (Natan et al, 2017b). The 50 data points were separately calculated as the mean FR over all repeats of each frequency.…”
Section: Sparsenessmentioning
confidence: 99%
“…This non-uniform distribution of selectivities suggested that the two cell clusters differentially process spatiotemporal information. FFI mediated by rapid synaptic activation of PVs (D'Souza et al, 2016) is a circuit motif shown to shape the temporal sensitivity of PNs in auditory cortex independent of stimulus adaptation (Li et al, 2014;Natan et al, 2017). Because the strength of FFI depends on the excitatory input to PNs and PVs and the latter's inhibition of PNs (Atallah et al, 2012), we compared the strength of excitatory inputs to patches and interpatches from different thalamocortical and intracortical pathways to L2/3 neurons in V1.…”
Section: Module-and Pathway-specific Synaptic Strengths Of Inputs To mentioning
confidence: 99%